Speed and Location Both Matter: Antigen Stimulus Dynamics Controls CAR-T Cell Response - Can Liu; Timothy Qi; J. Justin Milner; Yong Lu; Yanguang Cao; Yanguang Cao (Frontiers in Immunology, 2021)
Despite the success in B-cell malignancies, chimeric antigen receptor (CAR)-T cell therapies have not yet demonstrated consistent efficacy across all patients and tumor types, particularly against solid tumors. Higher rates of T cell exhaustion are associated with inferior clinical outcomes following CAR-T cell therapy, which is prevalent in solid tumors. T cell exhaustion may originate from persistent and chronic antigen stimulation by tumor cells that resist and/or evade T cell-mediated killing. We exploited CAR-T exhaustion with a classic negative feedback model (incoherent feedforward loop, IFFL) to investigate the balance between CAR-T cell activation and exhaustion under different antigen presentation dynamics. Built upon the experimental and clinical data, we hypothesize that the speed and anatomical location of antigenic stimulation are both crucial to CAR-T cell response. Chronic antigenic stimulation as well as the harsh tumor microenvironment present multiple barriers to CAR-T cell efficacy in solid tumors. Many therapeutic strategies are individually insufficient to improve of CAR-T responses against solid tumors, as they clear but one of the many barriers CAR-T cells face in solid tumors. A combination strategy targeting multiple barriers holds promise to improve CAR-T therapy in solid tumors.